PENGEMBANGAN ALAT DETEKSI ZONA SAMBARAN PETIR BERBASIS MULTISENSOR - Nugraha, Adi; Romi Wiryadinata; Felycia; Muhammad Ilham Daifullah (Politeknik Caltex Riau, 2025)
This study aims to develop a multisensor-based lightning strike zone detection device as an early warning system capable of identifying the risk level of lightning strikes in open areas in real time. The development specifically focuses on applying the Rolling Sphere Method to determine the boundaries between safe and hazardous zones based on open-space analysis. The sphere radius used in this method is processed into risk-zone calculation parameters, which are then implemented in a microcontroller system integrated with multisensors to monitor the user’s position and movement. The resulting zone mapping is visualized in the form of an ellipse illustrating a 50% lightning-strike probability within the safe area. The system provides automatic notifications through a smartphone when the user enters a hazardous zone (red zone), prompting immediate mitigation actions. Experimental results show that the device can accurately detect user movement and map risk zones with high precision. Thus, the proposed prototype has strong potential as an effective safety tool for reducing the risk of lightning-related injuries in open environments